Penerapan Pendekatan Sistem Terbuka ( Open System Approach ) dalam Meningkatkan Kualitas Pembelajaran di Era Digital - Farras Fadhilah; Rizka Amanda Putri; Muhammad Wafi Siregar; Abdul Fattah Nasution (Student Research Journal, 2024)
This research explores the application of an Open Systems Approach to improve the quality of learning in the digital era. The background of the research is based on the significant transformation in education due to the advancement of digital technology, which presents challenges in effective technology integration and equitable access. The research method used is library research, analysing literature related to the Open System Approach and learning quality in the digital era. The findings show three important aspects of implementing the Open Systems Approach: first, Collaborative Project-Based Learning (PBPK). Second, the flexibility of learning methods. Third, digital portfolio-based evaluation that facilitates documentation of work, encourages self-reflection, and enables more personalised feedback. The findings suggest that the Open Systems Approach, through the implementation of these strategies, can effectively improve the quality of learning in the digital era.